Literatur Review: Pengaruh Fitosterol terhadap Penurunan Kadar Kolesterol LDL dalam Darah - Nailul Amaniyatus Sya’bani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Excessive fat consumption can lead to increased cholesterol levels in the body, which in turn can trigger various serious health problems, including heart disease, blood vessel blockage, and even stroke. Blood cholesterol consists of two main types: LDL (Low-Density Lipoprotein) cholesterol, often referred to as bad cholesterol, and HDL (High-Density Lipoprotein) cholesterol, which plays a role in transporting cholesterol from the blood vessels to the liver for excretion. Elevated LDL cholesterol levels can cause plaque buildup on blood vessel walls, which narrows blood flow and increases the risk of various cardiovascular diseases. One method considered effective for lowering LDL cholesterol levels in the blood is by consuming phytosterols, compounds found naturally in various types of plants. Phytosterols have a structure similar to cholesterol and can compete with cholesterol for absorption in the intestine. This results in a decrease in the amount of cholesterol entering the body, thereby reducing total cholesterol levels and especially LDL cholesterol in the blood. Research shows that giving food or supplements containing about 3 grams of phytosterols per day to human subjects can reduce LDL cholesterol levels by up to 15%. Furthermore, phytosterols directly isolated from plants, such as green beans, have also been shown to significantly lower LDL cholesterol levels. Studies in mice fed phytosterols isolated from green beans showed a reduction in blood LDL cholesterol levels of more than 30%. This demonstrates the potential of phytosterols as a natural ingredient that can be used to support cholesterol management in the body. Although phytosterols have significant potential in lowering cholesterol levels, it is important to remember that consuming supplements or foods containing phytosterols should be done under the supervision and recommendation of a medical professional, especially for individuals with certain medical conditions or who are taking medications.